2021
DOI: 10.1021/acsami.1c11740
|View full text |Cite
|
Sign up to set email alerts
|

Step-Scheme Heterojunction between CdS Nanowires and Facet-Selective Assembly of MnOx-BiVO4 for an Efficient Visible-Light-Driven Overall Water Splitting

Abstract: The spatial separation and transport of photogenerated charge carriers is crucial in building an efficient photocatalyst for solar energy conversion into chemical energy. A step-scheme CdS/MnO x -BiVO4 photocatalyst was synthesized by spatial deposition of MnO x and one-dimensional (1D) CdS nanowires on a three-dimensional (3D) decahedron BiVO4 surface. The photocatalytic activity of CdS/MnO x -BiVO4 for the overall water-splitting reaction was investigated without sacrificial reagent under visible light irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…For example, Gogoi et al designed a robust photocatalyst based on CdS/MnO x -BiVO 4 /Pt, in which a step-scheme heterojunction was formed by the deposition of MnO x and CdS nanowires on the surface of decahedral BiVO 4 . [171] In this study, along with the optimization of the loading content, 5CdS/MnO x -BiVO 4 / Pt showed the highest H 2 and O 2 generation rates of 1.01 and 0.51 mmol g −1 h −1 , respectively, consistent with the theoretical stoichiometric ratio (Figure 8e-g). In this system, MnO x and Pt are capable of capturing photogenerated holes and electrons for surface reactions, respectively, which helps to realize accelerated charge transfer and suppressed charge recombination (Figure 8h,i).…”
Section: Photocatalytic Water Splittingsupporting
confidence: 81%
See 2 more Smart Citations
“…For example, Gogoi et al designed a robust photocatalyst based on CdS/MnO x -BiVO 4 /Pt, in which a step-scheme heterojunction was formed by the deposition of MnO x and CdS nanowires on the surface of decahedral BiVO 4 . [171] In this study, along with the optimization of the loading content, 5CdS/MnO x -BiVO 4 / Pt showed the highest H 2 and O 2 generation rates of 1.01 and 0.51 mmol g −1 h −1 , respectively, consistent with the theoretical stoichiometric ratio (Figure 8e-g). In this system, MnO x and Pt are capable of capturing photogenerated holes and electrons for surface reactions, respectively, which helps to realize accelerated charge transfer and suppressed charge recombination (Figure 8h,i).…”
Section: Photocatalytic Water Splittingsupporting
confidence: 81%
“…The experimental investigations revealed that the suitable band structure, superior electronic conductivity, and promoted light absorption endowed Ni-ZnIn 2 S 4 with high HER activity, which agrees with the theoretical calculations. Shifting beyond the introduction of impurities, formation of a solid solution caused Zhu et al [60] Pt-BP/CdS λ ≥ 420 nm Lactic acid 24.17 mmol g −1 h −1 Feng et al [159] CdS-P λ > 420 nm Na 2 S, Na 2 SO 3 194.3 µmol mg −1 h −1 Huang et al [126] V Zn -ZnS λ > 420 nm Na 2 S, Na 2 SO 3 337.71 ± 3.72 µmol g −1 h −1 Hao et al [63] N-ZnS 300 W xenon (Xe) lamp Lactic acid 243.61 µmol g −1 h −1 Tie et al [160] Cu 3 P/ZnS 250 W lamp Na 2 S, Na 2 SO 3 14 937 µmol g −1 h −1 Rameshbabu et al [64] MnS/D-PCN 300 W Xe lamp Methanol 670.5 µmol g −1 h −1 Zhang et al [65] CoP/Mn 0.2 Cd 0.8 S λ ≥ 420 nm Lactic acid 42.95 mmol g −1 h −1 Xiong et al [161] Mn 0.2 Cd 0.8 S/MnS λ ≥ 420 nm Na 2 S, Na 2 SO 3 995 µmol h −1 (0.05 g) Wang et al [162] Cu 2 S/CdS-DETA λ ≥ 420 nm Na 2 S, Na 2 SO 3 9.00 mmol g −1 h −1 (Pt) Li et al [163] Mo 2 C-In 2 S 3 500 W Xe lamp Lactic acid 535.58 µmol g −1 h −1 Ma et al [164] GO/Fe 2 P/In 2 S 3 Visible light Ascorbic acid 483.35 mmol g −1 h −1 Li et al [76] Ag-C 3 N 4 /SnS 2 λ ≥ 420 nm Na 2 S, Na 2 SO 3 1104.5 µmol g −1 h −1 Zhao et al [165] SnS 2 /TiO 2 300 W Xe lamp Methanol 652.4 µmol g −1 h −1 Sun et al [166] SnS 2 /g-C 3 N 4 Visible light Na 2 S, Na 2 SO 3 6305.18 µmol g −1 h −1 Jing et al [167] MoS 2 /CdS λ > 400 nm Lactic acid 13 129 µmol g −1 h −1 Zhuge et al [168] WO 3 @MoS 2 /CdS 300 W Xe lamp Lactic acid 8.2 mmol g −1 h −1 Zhang et al [169] ZnCo 2 S 4 /g-C 3 N 4 300 W Xe lamp Triethanolamine 6619 µmol g −1 h −1 Wang et al [78] Co 9 S 8 @CdIn 2 S 4 AM 1.5 Na 2 S, Na 2 SO 3 4604 µmol g −1 h −1 Yendrapati et al [79] Mn 0.2 Cd 0.8 S/NiWO 4 λ ≥ 420 nm Na 2 S, Na 2 SO 3 17.76 mmol g −1 h −1 Feng et al [80] Cu 2 ZnSnS 4 λ > 400 nm Na 2 S, Na 2 SO 3 68.68 µmol g −1 h −1 Wang et al [170] P-CdS LED None 76 µmol g −1 h −1 Shi et al [120] 5%CoP/P-CdS LED None 231 µmol g −1 h −1 Shi et al [120] 5CdS/MnO x -BiVO 4 λ > 400 nm None 1.01 mmol g −1 h −1 Gogoi et al [171] Carbon dots-CdS λ ≥ 420 nm None 2.55 µmol h −1 (50 mg) Zhu et al [172] by element doping is also ...…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, there are three approaches for the Z-scheme system, depending on the difference in the recombination way of the photogenerated electrons and holes, and corresponding summary is given in Table 3. [9,11,15,17,20,[89][90][91][92][93] The first one is the recombination via aqueous redox mediator shown in Figure 6b (i. e., I 3…”
Section: Bivo 4 -Based Photocatalytic Systemsmentioning
confidence: 99%
“…The remained photoexcited electrons in the OEP and holes in the HEP will recombine to complete the whole reaction cycle. Typically, there are three approaches for the Z‐scheme system, depending on the difference in the recombination way of the photogenerated electrons and holes, and corresponding summary is given in Table 3 [9,11,15,17,20,89–93] . The first one is the recombination via aqueous redox mediator shown in Figure 6b (i. e., I 3 − /I − , Fe 3+ /Fe 2+ , [Fe(CN) 6 ] 3− /[Fe(CN) 6 ] 4− , [Co(bpy) 3 ] 3+ /[Co(bpy) 3 ] 2+ ) [9,17,89,94] .…”
Section: Bivo4 Photocatalyst For Owsmentioning
confidence: 99%